Safety of the 9-Valent Human Papillomavirus Vaccine - Shimabukuro, Tom T. (Pediatrics, 2019)
BACKGROUND: The 9-valent human papillomavirus vaccine (9vHPV) was approved for females and males aged 9 to 26 years in 2014. We analyzed postlicensure surveillance reports to the Vaccine Adverse Event Reporting System (VAERS). METHODS: We searched VAERS data for US reports of adverse events (AEs) after 9vHPV from December 2014 through December 2017. We calculated reporting rates and conducted empirical Bayesian data mining to identify disproportional reporting. Physicians reviewed reports for selected prespecified conditions. RESULTS: VAERS received 7244 reports after 9vHPV: 31.2% among females, 21.6% among males, and for 47.2%, sex was not reported. Overall, 97.4% of reports were nonserious. Dizziness, syncope, headache, and injection site reactions were most commonly reported; the most commonly reported AEs were similar between females and males. Two reports of death after 9vHPV were verified; no information in autopsy reports or death certificates suggested a causal relationship with vaccination. Approximately 28 million 9vHPV doses were distributed during the study period; crude AE reporting rates were 259 reports per million 9vHPV doses distributed for all reports and 7 per million doses distributed for serious reports. Syncope (a known AE associated with human papillomavirus vaccination) and several types of vaccine administration errors (eg, administered at wrong age) exceeded the statistical threshold for empirical Bayesian data mining findings. CONCLUSIONS: No new or unexpected safety concerns or reporting patterns of 9vHPV with clinically important AEs were detected. The safety profile of 9vHPV is consistent with data from prelicensure trials and from postmarketing safety data of its predecessor, the quadrivalent human papillomavirus vaccine.